Role of Adult Learning Theories in the Development of Corporate Training in the USA - Iryna Lytovchenko (International Society of Philosophy and Cosmology, 2016)
The article presents the analysis of the role of adult learning theories in the development of corporate training in the USA. Considering that corporate education is part of the adult education system in this country, the author examines theories of organizational learning in the context of adult learning. The results of the study have revealed that adult education in the US is based on dif erent learning theories which should be viewed from the perspective of several main orientations: behaviorism, cognitivism, humanism, developmental theories, social learning, constructivism, which have dif erent philosophical background and, accordingly, different understanding of the nature and methodology of adult learning. Based on the results of the study it has been concluded that theories of organizational learning which explain motivation of students, their needs and goals, cognitive processes and other aspects of the learning in organizations and have had the main influence on the development of corporate education in the United States should be viewed in the context of the above-mentioned basic orientations to learning, too. From the methodological perspective, the research was based on interdisciplinary and systemic approaches. Thus, we used a set of interrelated research methods: comparative, structural, systemic-functional analyses, comparison and synthesis.